Does an Interdisciplinary Network Improve Dementia Care? Results from the IDemUck-Study - Kohler, Leonore; Meinke-Franze, Claudia; Hein, Jurgen; Fendrich, Konstanze; Heymann, Romy; Thyrian, Jochen Rene; Hoffmann, Wolfgang (Current Alzheimer Research, 2014)
Background: Most persons with dementia live at home and are treated in the primary care. However, the ambulatory health care system in Germany contains a lot of “interface problems” and is not optimized for the future challenges. Innovative concepts like regional networks in dementia care exist on a project level and need to be tested for efficacy to encourage implementation. The goal of the study is the scientific evaluation of an already existing regional dementia network. Methods: Prospective randomized controlled trial of 235 community-living elderly with dementia and their family caregivers of network treatment (n=117) compared to usual care (n=118) in a predominantly rural region. The allocation to intervention or control group was based on network membership of their General Practitioner. Intervention patients received diagnostic evaluation and subsequent treatment according to network guidelines. Main outcome measures were the early contact with a neurologic or psychiatric specialist and dementia-specific medication as well as quality of life of the patients, and as secondary outcomes caregiver burden and caregiver health-related quality of life. Results: Network patients were more likely to receive antidementive drugs (50.5 % vs. 35.8 %; p=0.035) and had more often contact to a neurologist (18.6 % vs. 2.8 %; p< 0.001). No group differences were found on patient’s quality of life nor overall effects or treatment by time effects. Intervention caregivers reported no significant improvements in health related quality of life measured by SF-36 and EQ-5D. Conclusion: The management of dementia patients in an interdisciplinary regional network solelyprovides measurable advantages with respect to the provision of dementia-specific medication and utilization of medical treatment i.e. referral rates to specialists. Further evaluation research is needed to identify relevant mechanismsof collaborative processes with respect to their impact on patient and caregiver related outcomes.
Keywords: Collaborative care